KESEHATAN REPRODUKSI REMAJA PADA SISWA SISWI SD AL IKHLAS LUMAJANG - Sri Wahyuningsih; Nurul Hayati; Achlish Abdillah; R. Endro Sulistyono; Syaifuddin Kurnianto (LP2M Universitas Jember, 2022)
Adolescence is a transitional age where a person experiences changes in his reproductive system which begins to function. Teenagers should be provided with information about reproductive health and various factors that may affect reproductive system. Purpose of this health promotion is for all 6th graders of SD Al Ikhlas Lumajang, Lumajang Regency to understand more about adolescent reproductive health and be able to practice it in everyday life. Service method uses counseling using Lectures with power point media, adolescent reproductive health education videos, X banners and leaflets. Results that are very supportive of the success of this community service activity are good coordination between presenters and committees, formulas and the school. Submission of material in the form of videos that are quite interesting for elementary school students who are classified as teenagers, there are discussions and questions and answers that are quite long, as well as door prizes for participants who dare to ask questions. Some of the inhibiting factors in this community service activity are the time and conditions during the pandemic so that the implementation of health protocols must be prioritized. The conclusion of this community service activity can be said to be successful. This can be observed in the level of attendance, the activeness of the participants. This activity took place in an orderly and good manner without experiencing significant obstacles. Follow-up that needs to be done is to continuously provide information on puberty and health, especially for new students